2022
DOI: 10.1021/acs.jpcb.2c03031
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of the Cardiac Ryanodine Receptor Type 2 (RyR2) Gating Mechanism

Abstract: Mutations in the cardiac ryanodine receptor type 2 (RyR2) have been linked to fatal cardiac arrhythmias such as catecholaminergic polymorphic ventricular tachycardia (CPVT). While many CPVT mutations are associated with an increase in Ca 2+ leak from the sarcoplasmic reticulum, the mechanistic details of RyR2 channel gating are not well understood, and this poses a barrier in the development of new pharmacological treatments. To address this, we explore the gating mechanism of the RyR2 using molecular dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…The importance of the U-motif residues I4218 and F4219, which we observed in the allosteric networks of most RyR1 and RyR2 model structures is underlined by the finding that the corresponding RyR2 residues I4172 and F4173 were found important for the interaction of the U-motif with the C-terminal domain and S6 helix, respectively (Kobayashi et al, 2022), and their alanine substitution led to the gain of function for RyR2 (Murayama et al, 2011). Greene et al (2022) observed in molecular dynamics simulations that the S45 linker of all monomers has to assume the "open" position for the channel to be open, suggesting their intimate involvement with the transitions between macrostates. The residues T4825, I4826, S4828, and S4829, present in several branches of the activation and inhibition networks, were shown to be involved in RyR1 gating (Murayama et al, 2011), and the mutation T4825I was shown to weaken RyR1 inhibition by Ca 2+ (Gomez et al, 2016).…”
Section: Comparison With Previous Studiesmentioning
confidence: 75%
“…The importance of the U-motif residues I4218 and F4219, which we observed in the allosteric networks of most RyR1 and RyR2 model structures is underlined by the finding that the corresponding RyR2 residues I4172 and F4173 were found important for the interaction of the U-motif with the C-terminal domain and S6 helix, respectively (Kobayashi et al, 2022), and their alanine substitution led to the gain of function for RyR2 (Murayama et al, 2011). Greene et al (2022) observed in molecular dynamics simulations that the S45 linker of all monomers has to assume the "open" position for the channel to be open, suggesting their intimate involvement with the transitions between macrostates. The residues T4825, I4826, S4828, and S4829, present in several branches of the activation and inhibition networks, were shown to be involved in RyR1 gating (Murayama et al, 2011), and the mutation T4825I was shown to weaken RyR1 inhibition by Ca 2+ (Gomez et al, 2016).…”
Section: Comparison With Previous Studiesmentioning
confidence: 75%
“…3 D) and left ventricular fractional shortening rate (FS) ( Fig. 3 E) indicators, which showed that OpiCa1 and OpiCa1-PEG-PLGA were completely restored to normal, and PEG-PLGA had a gentle trend of partial recovery [ 49 , 50 ]. In all, The results from survival rate and echocardiography indicated that OpiCa1-PEG-PLGA nanoparticles retain the activity of OpiCa1 and have the effect of antagonizing the lethal acute heart failure induced by Caff and Epi.…”
Section: Resultsmentioning
confidence: 99%